To the Question of Criminological Security in the Use of Cryptocurrency - E. V. Bochkareva (Сибирское юридическое обозрение, 2019)
The Author examines various approaches to the definition of cryptocurrency, the issues of legislative regulation of cryptocurrency in Russia, proposes measures to counter crimes using cryptocurrency. Based on the study, the Author concludes that in order to regulate cryptocurrency transactions, as well as in order to create a uniform judicial practice in cases related to cryptocurrency, it is necessary to create a unified regulatory framework on the subject matter. The Author proposes to legislatively fix the definition of cryptocurrency, the conditions for its issuance, storage and execution of transactions with it, as well as the circle of persons authorized to carry out operations to create, exchange, etc. with cryptocurrency; conduct training of specialists in the field of cryptocurrency through training courses, lectures, seminars, conferences, etc., including abroad, as well as to ensure the exchange of experience between experts in the field of cryptocurrency; create a technical base in law enforcement to track cryptocurrency transactions; to ensure the formation of scientific schools in the field of cryptocurrency.